Korowe mechanizmy pamięci w ujęciu funkcjonalnym. Perspektywa biolingwistyczna - Krysiak, Adrian P. (Investigationes Linguisticae, 2010)
This paper presents correlations between language and memory with specific focus given to working memory. Cortico-cortical and cortical-striatal-cortical interactions for language processing are proposed, and therein, a neurocognitive network connecting temporal, parietal and prefrontal cortices is discussed. This approach is explored with the framework of Baddeley’s model of working memory, language origins, and some psychopathologies and genetic linguistics.